Assessment of inflammatory markers in otosclerosis patients - Arli,Cengiz (2020)
Abstract Introduction Otosclerosis is an idiopathic disease characterized by new bone formation in foci of the human otic capsule. It is more common in Caucasian populations; affecting females twice as often as males. Its etiopathogenesis has not yet been fully elucidated. Objective The aim of this study was to investigate the relationship between otosclerosis and white blood cell and thrombocyte counts, mean platelet volume, neutrophil lymphocyte ratio, and the platelet lymphocyte ratio. Methods This retrospective case-control study was conducted in the outpatient clinic Mustafa Kemal University, in the department of otolaryngology, between 2015 and 2018. A total of 30 patients with an established diagnosis of otosclerosis were compared to a control group of 30 healthy subjects, matched for age, gender and body mass index. The white blood cell, thrombocyte, mean platelet volume, neutrophil lymphocyte ratio and platelet lymphocyte ratio values were calculated for all participants. Results There was no statistically significant difference between the groups with respect to age, gender, or body mass index, or for the mean neutrophil lymphocyte ratio, platelet lymphocyte ratio, white blood cell, or thrombocyte values (p > 0.05). A statistically significant difference was determined between the groups for the mean platelet volume values. The mean platelet volume values were lower in the otosclerotic patients (p = 0.047). Conclusion These results show that neutrophil lymphocyte ratio, platelet lymphocyte ratio, white blood cell and thrombocytes should not be used to predict otosclerosis, but suggest that mean platelet volume may be a negative predictive marker.